SHIP FOR SOUTH EAST ASIAN YOUTH PROGRAM (SSEAYP) DALAM SOFT DIPLOMACY INDONESIA DIKAWASAN ASEAN-JEPANG - Aliyah, Ayu; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research is an international relations in diplomacy studies which describes about the efforts and impacts of Ship for South East Asian Youth Program (SSEAYP) toward Indonesia cultural diplomacy. SSEAYP was launched based on the respective Joint Statements issued in 1974 between Japan and five countries of ASEAN region. And now this program followed by ten ASEAN countries. The aims of the program are to promote friendship and mutual understanding among youths of Japan and ASEAN countries, broaden their perspective on the world and introducing their culture to one another.This is qualitative research which used descriptive explanative methods. This paper used the neo-realist perspective and cultural diplomacy theory proposed by Joseph Nye and Alexander Vuving. The object of this research is Ship for South East Asian Youth Program.The result of this research explained Indonesian efforts with cultural diplomacy to take advantage of this program to promote our culture by shown it during the program. This program gives some positives impacts to Indonesian diplomacy especially in youth development and culture aspect, because after this program ASEAN countries and Japan will know about Indonesian culture, and alumnus of SSEAYP Indonesia can be the next future leader. This program give impacts to strengthen the friendship and mutual understanding between ASEAN countries and Japan.Key Words: Cultural diplomacy, Indonesia, SSEAYP, Youth, Efforts,